Chest pain units or chest pain algorithm? - Christ, M.; Dormann, H.; Enk, R.; Popp, S.; Singler, K.; Müller, C.; Mang, Harald (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2014)
A large number of patients present to the emergency department (ED) for evaluation of acute chest pain. About 10-15% are caused by acute myocardial infarction (MI), and over 50% of cases are due to noncardiac reasons. Further improvement for chest pain evaluation appears necessary.What are current options to improve chest pain evaluation in Germany?A selective literature search was performed using the following terms: "chest pain", "emergency department", "acute coronary syndrome" and "chest pain evaluation".A working group of the German Society of Cardiology published recommendations for infrastructure, equipment and organisation of chest pain units in Germany, which should be separated from the ED of hospitals and be under the leadership of a cardiologist. A symptom-based decision for acute care would be preferable if all differential diagnoses of diseases could be managed by one medical specialty: However, all four main symptoms of patients with acute MI (chest pain, acute dyspnea, abdominal pain, dizziness) are also caused by diseases of different specialties. Evaluation and treatment of acute chest pain by representatives of one specialty would lead to over- or undertreatment of affected patients. Therefore we suggest a multidisciplinary evaluation of patients with acute chest pain including representatives of emergency and critical care physicians, cardiologists, internists, geriatricians, family physicians, premedics and emergency nurses. Definition of key indicators of performance and institutionalized feedback will help to further improve quality of care.
EVALuna2:10542

Effects of Monetary Incentives in Physician Groups: A Systematic Review of Reviews - Heider, Ann-Kathrin; Mang, Harald (Applied Health Economics and Health Policy, 2020)
Background Reimbursement systems that contribute to the cooperation and integration of providers have become increasingly important within the healthcare sector. Reimbursement systems not only serve as payment mechanisms but also provide control and incentive functions. Thus, the design of reimbursement systems is extremely important. Objectives The aims of this systematic review were to describe and gain a better understanding of the effects of monetary incentives in the setting of physician groups. Methods In January 2020, we searched the MEDLINE (PubMed), Cochrane Library, CINAHL, PsycINFO, EconLit, and ISI Web of Science databases as well as the gray literature and authors' personal collections. Results We included 21 reviews containing seven different incentive schemes/initiatives. The study settings and outcome measures varied considerably, as did the results within the incentive schemes and initiatives. However, we found positive effects on process quality for two types of incentives: pay-for-performance and accountable care organizations. The main limitations of this review were the variations in study settings and outcome measures of the studies included. Conclusions Monetary incentives in healthcare are often implemented as a control measure and are supposed to increase quality of care and reduce costs. The heterogeneity of the study results indicates that this is not always successful. The results reveal a need for research into the effects of monetary incentives in healthcare.
CRIS-Team WoS Importer:2020-04-10

Effects of Non-monetary Incentives in Physician Groups-A Systematic Review - Heider, Ann-Kathrin; Mang, Harald (American Journal of Health Behavior, 2023)
Objectives: Healthcare expenditures in western countries have been rising for many years. This leads many countries to develop and test new reimbursement systems. A systematic review about monetary incentives in group settings indicated that a sole focus on monetary aspects does not necessarily result in better care at lower costs. Hence, this systematic review aims to describe the effects of non- monetary incentives in physician groups. Methods: We searched the databases MEDLINE (PubMed), The Cochrane Library, CINAHL, PsycINFO, EconLit, and ISI Web of Science. Grey literature search, reference lists, and authors' personal collection provided additional sources. Results: Overall, we included 36 studies. We identified 4 categories of interventions related to non-monetary incentives. In particular, the category of decision support achieved promising results. However, design features vary among different decision support systems. To enable effective design, we provide an overview of the features applied by the studies included. Conclusions: Not every type of non-monetary incentive has a positive impact on quality of care in physician group settings. Thus, creating awareness among decision-makers regarding this matter and extending research on this topic can contribute to preventing implementation of ineffective incentives, and consequently, allocate resources towards tools that add value.
CRIS-Team Scopus Importer:2023-09-01

Integration of Risk Scores and Integration Capability in Electronic Patient Records - Heider, Ann-Kathrin; Mang, Harald (Applied Clinical Informatics, 2022)
BACKGROUND: Digital availability of patient data is continuously improving with the increasing implementation of electronic patient records in physician practices. The emergence of digital health data defines new fields of application for data analytics applications, which in turn offer extensive options of using data. Common areas of data analytics applications include decision support, administration, and fraud detection. Risk scores play an important role in compiling algorithms that underlay tools for decision support. OBJECTIVES: This study aims to identify the current state of risk score integration and integration capability in electronic patient records for cardiovascular disease and diabetes in German primary care practices. METHODS: We developed an evaluation framework to determine the current state of risk score integration and future integration options for four cardiovascular disease risk scores (arriba, Pooled Cohort Equations, QRISK3, and Systematic Coronary Risk Evaluation) and two diabetes risk scores (Finnish Diabetes Risk Score and German Diabetes Risk Score). We then used this framework to evaluate the integration of risk scores in common practice software solutions by examining the software and inquiring the respective software contact person. RESULTS: Our evaluation showed that the most widely integrated risk score is arriba, as recommended by German medical guidelines. Every software version in our sample provided either an interface to arriba or the option to implement one. Our assessment of integration capability revealed a more nuanced picture. Results on data availability were mixed. Each score contains at least one variable, which requires laboratory diagnostics. Our analysis of data standardization showed that only one score documented all variables in a standardized way. CONCLUSION: Our assessment revealed that the current state of risk score integration in physician practice software is rather low. Integration capability currently faces some obstacles. Future research should develop a comprehensive framework that considers the reasonable integration of risk scores into practice workflows, disease prevention programs, and the awareness of physicians and patients.
CRIS-Team Scopus Importer:2022-09-16

Patients With Syncope in a German Emergency Department: Description of Patients and Processes - Gueldner, Sebastian; Langada, Viktoria; Popp, Steffen; Heppner, Hans Jürgen; Mang, Harald; Christ, Michael (Deutsches Ärzteblatt international, 2012)
Background: We studied the characteristics and resource utilization of patients with syncope in a German emergency department (ED). Methods: We carried out a single-center retrospective analysis of patients with syncope who presented to the ED of the Klinikum Nürnberg (a municipal hospital in Nuremberg, Germany). Results: Among the 28 477 patients who presented to the ED from 15 May 2009 to 30 September 2009, 440 (1.5%) presented with syncope. Their mean age was 62 years (standard deviation, 20 years); 50.4% were women, 43.4% were over age 70, 11.8% had cardiogenic and 4.8% neurological syncope, and 18.2% had more than two comorbid conditions. 20.7% were discharged after evaluation in the ED, 14.1% were brielfly hospitalized in the ED's clinical observation unit, and 56.6% were admitted to one of the hospital's specialty wards. 8.6% left the ED against medical advice. All of the syncope patients were evaluated by history-taking, physical examination, and 12-lead electrocardiogragraphy (ECG); ECG revealed abnormal findings in 36.4% of patients. Nearly all patients also underwent laboratory testing, which revealed hyponatremia (a serum sodium concentration under 130 mmol/L) in 5.9% and a serum creatinine level above 2 mg/dL in 5.3%. Many underwent technology-intensive tests such as cranial computed tomography (129 patients), but these tests only rarely yielded abnormal findings (3.1%). 27% of the syncope patients underwent Doppler ultrasonography of the vessels supplying the brain, with abnormal findings in 6.7% of cases. (Orthostatic testing was performed in 14.5% of the patients and was positive in 26.6%.) Conclusion: Many patients presenting with syncope to a German ED are elderly, and multiple comorbidities are common. Technology-intensive testing in patients with syncope has a low diagnostic yield and consumes resources. The introduction of standards for the evaluation of syncope in the ED would be helpful.
CRIS-Team Scopus Importer:2022-09-26

Screening for 4MRGN in German emergency departments - Dormann, H.; Eichelsdoerfer, L.; Karg, M. V.; Mang, Harald; Schumacher, A. -K. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2020)
Background Multiresistant Gram-negative bacteria (MRGN) are a growing clinical problem. The practical implementation of the recommendation of the Commission for Hospital Hygiene and Infection Prevention (KRINKO) for screening according to 4MRGN (MRGN resistant to all four categories of antibiotics), however, varies considerably between emergency departments. Objectives This study is intended to give an overview of the status quo and the quality assurance of 4MRGN screening and to show possibilities for process optimization. Materials and methods In 2018, a web-based survey was conducted among emergency room directors and directors of clinics in the Association of Hospital Directors in Germany (VKD). Results The response rate of the 267 clinics surveyed was 31.1%. In all, 83.4% of the emergency rooms surveyed routinely screen for multiresistant pathogens. In 71.8% a standard procedure (SOP) is defined and 82.0% of the test criteria refer to the KRINKO recommendation. Only 39.7% of the clinics follow it without in-house adaptation. No clinic can give an exact number of actual risk patients per year. According to the median, 55 patients in an emergency room met the KRINKO screening criteria in 2017. Only 40 patients were screened for suspected 4MRGN. Quality assurance of the screening was performed by 41.0% of emergency departments. The responsibility lies mainly with the hygiene department. Conclusions Even if screenings are carried out as far as possible, there is a lack of standardization in the recording of case numbers and quality assurance. Therefore, it can be assumed that there are numerous individuals with undetected 4MRGN. As a quality indicator, SOPs could clearly assign responsibilities and improve infection hygiene.
CRIS-Team WoS Importer:2020-05-15

Severity illness scoring systems for early identification and prediction of in-hospital mortality in patients with suspected sepsis presenting to the emergency department - Geier, Felicitas; Popp, Steffen; Greve, Yvonne; Achterberg, Andreas; Gloeckner, Erika; Ziegler, Renate; Mang, Harald; Christ, Michael; Heppner, Hans Jürgen (Wiener Klinische Wochenschrift, 2013)
The in-hospital mortality of patients with severe sepsis and septic shock (SSSS) is high. In this study we examined the diagnostic and prognostic accuracy of the emergency severity index (ESI), the modified early warning score (MEWS), and the mortality in emergency department (ED) sepsis (MEDS) score. This is a single-centre, prospective and observational study of 151 consecutive patients presenting to the ED of the Nuremberg Hospital with suspected sepsis (age 68.3 ± 18 years, 54.3 % men, 45 % with SSSS, in-hospital mortality of SSSS: 27.8 %). In this study, 37.7 % of the studied patients had a urinary tract infection (n = 57/151), 33.8 % a pneumonia (n = 51/151), 8.6 % an acute abdominal infection (n = 13/151), and in 12.6 % the focus of infection was not further specified or identifiable (n = 19/151). The diagnostic and prognostic accuracy was analyzed by means of the receiver operating characteristic (ROC) curve. The areas under curve (AUC) in terms of diagnostic accuracy were 0.609, 0.641, and 0.778 for the ESI, MEWS, and MEDS score respectively. The AUCs concerning prognostic accuracy were 0.617, 0.642, and 0.871 for ESI, MEWS, and MEDS score respectively. By using the MEDS score systematically, critically ill patients with sepsis could be detected in the ED. Finally, the MEDS score provides the basis for a risk adjusted disposition management that follows objective criteria. © 2013 Springer-Verlag Wien.
CRIS-Team Scopus Importer:2022-09-26
Keywords: early identification; emergency department; prognosis; sepsis; severityillness scoring systems

The prevalence and prognostic significance of near syncope and syncope: a prospective study of 395 cases in an emergency department (the SPEED study) - Greve, Yvonne; Geier, Felicitas; Popp, Steffen; Bertsch, Thomas; Singler, Katrin; Meier, Florian; Smolarsky, Alexander; Mang, Harald; Mueller, Christian; Christ, Michael (Deutsches Ärzteblatt international, 2014)
The prognostic significance of near-syncope has not yet been adequately characterized.We collected prospective data on a consecutive series of patients seen in an emergency department with syncope (brief loss of consciousness, usually with loss of muscle tone) or near-syncope (a feeling that syncope is about to occur, but without actual loss of consciousness or muscle tone). We report on the prevalence, etiology, and prognosis of such events (the SPEED study). Patients were followed up at 30 days and at 6 months after the event.From 17 July to 31 October 2011, 395 patients were seen in the emergency department for a chief complaint of syncope or near-syncope (3% of all emergency patients). Their median age was 70 years, and 55% were men. 62% had experienced syncope, and 38% near-syncope. The patients with near-syncope were younger than those with syncope ( 63 vs. 72 years, p < 0.014) and were also more commonly male (63% vs. 49%, p = 0.006). The two patient groups did not differ significantly with respect to their measured laboratory values and vital parameters or their accompanying medical conditions. Hospitalizations were more common for syncope than for near-syncope (86% vs. 70%, p < 0.001). Etiologies were similarly distributed in the two patient groups, with the main ones being reflex syncope, orthostatic syncope, cardiac syncope, and syncope of uncertain origin. In all, 123 of 379 patients (32%) had further undesired events within 30 days of the event. Multivariable logistic regression revealed that age, heart rate, and renal dysfunction were independent predictors of undesired events, while the type of syncope was not.Patients with near-syncope do not differ to any large extent from patients with syncope with respect to the features studied. The diagnostic evaluation should be similar for patients in the two groups.
EVALuna2:10506

Versorgungsprozesse von Patienten mit Verdacht auf Sepsis in einer deutschen Notaufnahme - Geier, F.; Greve, Y.; Popp, S.; Achterberg, A.; Gloeckner, E.; Ziegler, R.; Heppner, Hans Jürgen; Mang, Harald; Christ, Michael (Deutsche Medizinische Wochenschrift, 2014)
Background: The in-hospital mortality of patients with severe sepsis and septic shock (ssss) is high. Of note, little is known about the health care situation of patients with sepsis in German emergency departments. The aim of the study was to analyze whether sepsis patients are treated according to current guidelines, to identify the treatment sites within the hospital and to evaluate the death rate of affected patients during index hospitalization. Patients and methods: In this single-centre, prospective and observational trial we analyzed consecutive patients with complaints of sepsis during August and September 2012. Results: During the study period 151 patients presented with complaints of sepsis (age 68.3 ± 18 years, 54.3 % men, 45 % with ssss, in-hospital mortality of the overall cohort: 14.6 %). The Surviving Sepsis Campaign three hour bundle (lactate, blood cultures, broad spectrum antibiotics, and volume) was carried out in 54.2 % of patients with ssss. In case of ssss, broad spectrum antibiotics were initiated in the emergency department in 85.4 %. Patients with ssss were admitted to wards with usual care in 67.2 %, in 32.8 % they were admitted to an intensive or intermediate care unit. The in-hospital mortality of patients with ssss during their index hospitalization was 27.8 %. Conclusion: Despite the high in-hospital mortality rate, more than two thirds of the patients with ssss were admitted to wards with usual care. We call for action 1) to early identify affected patients, 2) to provide adequate risk stratification tools and 3) to realize an early disposition of patients to the appropriate care units.
CRIS-Team Scopus Importer:2022-09-26
Keywords: disposition; emergency department; guideline-based health care; in-hospital mortality; sepsis